Literature Review: Analysis and Validation of the Effectiveness of Antidiabetic Drugs in the Biological Matrix Using the HPLC (High Performance Liquid Chromatography) Method - Syahwa Aulia Fernanda; Naila Tirsta Az-zahra; Teresa Savitri Setyoasih; Ghefira Najwa Akmila; Sekar Bekti Pertiwi; Sabrina Maharani (Al Makki Publisher, 2025)
High-Performance Liquid Chromatography (HPLC) is a widely used analytical method for the separation, identification, and quantification of compounds in complex biological matrices, such as plasma, serum, and urine. This article discusses the analysis and validation of the effectiveness of antidiabetic drugs using HPLC, focusing on sample preparation, column selection, mobile phase, and detectors used. Method validation is performed to ensure parameters such as specificity, linearity, precision, accuracy, limit of detection (LOD), and limit of quantification (LOQ) are met. Literature study from 18 journals showed that HPLC is a sensitive, specific, and efficient method for antidiabetic drug analysis. Preparation techniques such as protein precipitation and solid-phase extraction provide optimal results in minimizing biological matrix interferences. In addition, the Photodiode Array (PDA) detector proved superior in terms of sensitivity and analyzability at low concentrations compared to other detectors. By fulfilling all validation parameters, HPLC can be relied upon as a primary method for the analysis of antidiabetic drugs in biological matrices.